Indonesian Law Students' Experiences in Mastering Legal Vocabulary through a Legal English Words Application - Saumi, Rahma Ibtida; Widya Wulandari; Abdul Syahid (Universitas Negeri Medan, 2025)
This study analyses the legal vocabulary acquisition experiences of law students in Indonesia using a Legal English application with focus on its use as an educational tool in digital environment. A qualitative case study approach was adopted whereby data were gathered from 5 th semester law students in one of the State Islamic Institute in Central Kalimantan Indonesia who implemented the application for a week. Results show that although students perceived the app as easy to use and helpful for improving their legal vocabulary, several issues were revealed as necessitating urgent attention, especially the app’s ability to monitor progress. Learners appreciated several of the lessons which the instructors felt were fun and linked to law practice. However, such assessments of the app were constrained by app limitations and short usage duration. The app and its accompanying programs contributed to some degree, to the development of vocabulary suggesting that more varied interactions and adequate tracking features should accompany such programs.